Performance analysis of stator structure in divided teeth outer rotor embedded permanent magnet synchronous motor: salient pole stator vs segmented stator - Hairulnizam, Hairul F.; Misron, Norhisam; Ibrahim, Nur A.; Muhammad, Ezwan; Vaithilingam, Chockalingam A. (Electromagnetics Academy, 2024)
To improve torque characteristics, this study proposes an upgrade over the standard salient pole stator in a Permanent Magnet Synchronous Motor (PMSM) using a segmented stator. The rotor is externally oriented and has a permanent magnet (PM) incorporated in it. The structure is studied theoretically through flux linkage analysis, torque production, and magnetic circuit model (MCM) analysis. Next, the finite element technique (FEM) is used to model the suggested motor and the salient pole stator, both of which have the same size. Next, a comparison is made between the simulation findings and the static torque, PM demagnetization, flux linkage, magnetic flux density distribution, and average and maximum torque. The proposed design results in a 79.97% increase in average torque, a 90.89% increase in maximum torque, and a 3.02% decrease in cogging torque.